Determinants and perceptions of the utilization of tetanus toxoid immunization among reproductive-age women in Dukem Town, Eastern Ethiopia: a community-based cross-sectional study - Meseret Delesa Anatea; Tesfaye Hambisa Mekonnen; Berihun Assefa Dachew (BMC, 2018)
Abstract Background Maternal and neonatal tetanus (MNT) is still the major public health problem in about 25 countries, mainly in Africa and Asia. However, the utilization of intervention strategies, like tetanus toxoid (TT) immunization remains low in these countries. In Ethiopia, only 49% of the pregnant mothers received TT2+ in 2016. This study was designed to evaluate perceptions and factors affecting the utilization of TT immunization among reproductive-age women in Dukem town, Eastern Ethiopia, 2016. Methods We conducted a community-based cross-sectional study from May to October 2016. A simple random sampling method was employed to select samples of 422 women. Data were collected using a, pretested semi-structured and a face-to-face interviewer-administered questionnaire. We entered data in to Epi Info version 7 and analyzed them by SPSS version 20 software. Odds ratios and a 95% CI at 0 < 0.05 p-value were calculated to ascertain the significance of associations. Results Response rate was 98.6% (N = 416). Mean age with standard deviation was 29.25± 5.11 years, and average family size was 4.19. Our study showed the utilization of TT immunization was 39.2% (N = 163). Of the participants, 33.9% (N = 141) had never been vaccinated. ANC follow up service [AOR: 2.56, 95% CI: (1.18, 5.49)], distance from health facilities [AOR: 2.27, 95% CI: (1.27, 4.09)], knowing vaccination date [AOR: 1.98, 95% CI: (1.23, 3.18)], having a TV set in the house [AOR: 1.80, 95% CI: (1.11, 2.917)], maternal education [AOR: 1.41, 95% CI: (1.84, 2.30), and place of delivery [AOR: 1.19, 95% CI: (1.00, 1.43)] were factors significantly associated with the utilization of TT immunization. Conclusions This study indicated the utilization of TT immunization was low. ANC service follow up, distance from health facilities, knowing vaccination date, having a TV in the house, mothers' educational status, and place of delivery were significant predictors. Our study suggests that policymakers and other stakeholders should consider the need for increasing access to maternal education, like basic adult education, ANC follow up services, providing accessible health facilities, improving varieties of communication media, promoting female occupational status, and providing appropriate vaccination cards.